Validation of the Precalculus didactic unit produced at the Distance State University of Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2023)
The aim of the study is to validate the didactic unit (DU) Pre-Calculus according to the perception of students and teachers. A sequential mixed methodology is used. The results indicate an improvement in the knowledge of the course topics, thanks to the use of the DU as an educational material. 76% of the students and 100% of the teachers consider the DU is useful or extremely useful to achieve the course objectives. The solution manual and exercises are the elements of the DU that students value as most useful. There is no evidence that demonstrates widespread dissatisfaction with the extension of the DU. It is concluded that both students and teachers are satisfied with the characteristics of the DU.